Fabrication of Graphene Oxide Reinforced Biocomposite: Recycling of Postconsumed Footwear Leather - Rashedul Islam; Md Ashikur Rahaman Noyon; Thuhin Kumar Dey; Mamun Jamal; Rajasekar Rathanasamy; Moganapriya Chinnasamy; Md. Elias Uddin (Advances in Polymer Technology)
The increasing concerns about solid waste disposal have led to the development of innovative strategies for repurposing waste materials. This paper describes a simple solution casting process for recycling postconsumed footwear leather fiber (PCF) into a biocomposite film reinforced with graphene oxide (GO) and polyvinylpyrrolidone (PVP). PVP was utilized as a compatibilizer to strengthen the interfacial bonding of GO and leather fiber via π–π interactions. UV–visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy were used to examine the material dispersibility bonding between GO and PCF, structural properties, thermal properties, and surface morphology of the biocomposite films, respectively. Compared to pure PCF film, the oxygen transmission rate of the prepared biocomposite films is elevated by 64% as well as the biodegradability rate is intensified up to 60%. In addition, the film’s tensile strengths are raised by 216%, while their elongation at break is increased by 164.64% as compared with PCF. The versatility of these eco-friendly and biodegradable composite films extends to its possible applications in packaging and interior design. The outcomes of the research reveal the viability of manufacturing affordable and sustainable biocomposites through the utilization of waste leather from consumed footwear.